2017
DOI: 10.1159/000479254
|View full text |Cite
|
Sign up to set email alerts
|

End-Stage Renal Disease, Inflammation and Cardiovascular Outcomes

Abstract: Despite marked improvements in renal replacement therapy during the last 30 years, the age-adjusted mortality rate in end-stage renal disease (ESRD) patients is still unacceptably high and comparable to that of many malignancies. Cardiovascular disease (CVD) remains the major cause of morbidity and mortality in ESRD patients. However, traditional risk factors can only partially explain the high premature cardiovascular burden in this population. Nontraditional risk factors, including persistent low-grade infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
111
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 31 publications
1
111
1
2
Order By: Relevance
“…Abnormal ABI has been shown to be well correlated with systemic disease burden of atherosclerosis, which is a strong predictor of MACE . On the other hand, accumulating evidence demonstrated that an elevation of cTn is specific to myocardial damage and hs‐CRP reflects systematic atherosclerotic burden and activity even in ESKD patients . As multiple organ disorder causes markedly higher systemic adverse events, these observations suggest that biomarker approach complements the risk assessment that cannot be identified by ABI alone, and their combination could provide better risk stratification of ESKD patients treated with HD.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal ABI has been shown to be well correlated with systemic disease burden of atherosclerosis, which is a strong predictor of MACE . On the other hand, accumulating evidence demonstrated that an elevation of cTn is specific to myocardial damage and hs‐CRP reflects systematic atherosclerotic burden and activity even in ESKD patients . As multiple organ disorder causes markedly higher systemic adverse events, these observations suggest that biomarker approach complements the risk assessment that cannot be identified by ABI alone, and their combination could provide better risk stratification of ESKD patients treated with HD.…”
Section: Discussionmentioning
confidence: 99%
“…CRP, an acute phase reactant, is known to be directly associated with malnutrition in HD patients [31]. Persistent low-grade inflammation is common among patients with chronic renal disease [32]. Moreover, malnutrition in CKD patients is associated with a proinflammatory state [33].…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, the liquid imbalance in these patients, defined by both sodium retention and loss of RRF, promotes endothelial dysfunction and progression of inflammation/ oxidative stress, contributing to an increased MCP-1 production resulting in more adverse effects on the cardiovascular system. Indeed, fluid overload is included in promoting the inflammation factors [11].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis and cardiovascular disease in this patient population are mainly affected by nontraditional risk factors, including persistent low-grade inflammation, metabolic acidosis, volume overload, and comorbidities. The causes of inflammation are multifactorial and include imbalance between increased production and decreased removal of pro-inflammatory cytokines, oxidative stress, factors linked to dialysis treatment, and chronic and recurrent infections related to dialysis access [11].…”
mentioning
confidence: 99%